Novel pharmacotherapy for burn wounds: what are the advancements - Hamblin, Michael R. (Expert Opin Pharmacother, 2018)
INTRODUCTION: The prognosis for severe burns has improved significantly over the past 50 years. Meanwhile, burns have become an affliction mainly affecting the less well-developed regions of the world. Early excision and skin grafting has led to major improvements in therapeutic outcomes. AREAS COVERED: The purpose of this article is to survey the use of pharmacotherapy to treat different pathophysiological complications of burn injury. The author, herein, discusses the use of drug treatments for a number of systemic metabolic disturbances including hyperglycemia, elevated catabolism, and gluconeogenesis. EXPERT OPINION: Advancements in personalized and molecular medicine will make an impact on burn therapy. Similarities between severe burns and other critically ill patients will lead to cross-fertilization between different medical specialties. Furthermore, advances in stem cells and tissue regeneration will lead to improved healing and less lifelong disability. Indeed, research in new drug therapy for burns is actively progressing for many different complications.